PEMANFAATAN ZnO/ZEOLIT UNTUK DEGRADASI AIR GAMBUT MENGGUNAKAN METODE OZONOLISIS DAN PENGARUH TERHADAP KADAR BESI - Zilfa, Z.; Yulizar Yusuf; Joya Patricia Ambri (Departemen Kimia Universitas Andalas, 2025)
Peat water is one of the surface water sources that is difficult to utilize because it has poor quality with high Organic content (Humic Acid and Fulvic Acid), and Inorganic such as Iron. The application of the Advanced Oxidation Process (AOP) method using an ozone generator can be used in the degradation of peat water, to obtain effective degradation results, a ZnO/Zeolite catalyst is added. This study aims to determine the effect of ZnO/Zeolite catalyst utilization on peat water degradation by Ozonolysis method on Fe, COD, BOD, Nitrite, and Nitrate levels, and TSS values. The parameters tested included determining the optimum conditions for peat water degradation on Fe. The results obtained from the degradation process with ozone is for 15 minutes using ZnO/Zeolite as much as 0.2 grams, peat water sample volume of 20 mL. After the degradation process was carried out at optimum conditions, the Fe content was found to be 0.11 mg/L. The results of the test parameters were within the limits of the quality standards used. Based on these data, it can be said that the decrease in Fe metal concentration values in peat water by ozonolysis is more effective with the addition of ZnO/zeolite catalyst at optimum conditions.